Tunable Non-Linear Dynamics in Nano-Electromechanical Systems (NEMS) Driven by Casimir Force Modulation - Vishal Yadav; Sanya Desai; Manivone Keolavong (Journal of Tecnologia Quantica, 2025)
Nano-electromechanical systems (NEMS) exhibit remarkable sensitivity and non-linear behavior at the nanoscale, making them ideal candidates for applications in sensing, actuation, and quantum technologies. The Casimir force, a quantum phenomenon resulting from vacuum fluctuations, becomes significant at small scales and has the potential to modulate the dynamics of NEMS. This research investigates the tunable non-linear dynamics in NEMS driven by Casimir force modulation, exploring the ability to induce non-linear behaviors such as bistability, hysteresis, and chaotic motion. The primary objective of this study is to understand how Casimir force modulation can be used to control the non-linear dynamics of NEMS, providing a new method for tuning their mechanical responses. The research combines both theoretical simulations and experimental validation, examining the effects of Casimir force on different materials, including graphene, silicon, and carbon nanotubes, across various modulation strengths. The results show that Casimir force modulation can significantly enhance non-linear behaviors in NEMS, with graphene-based systems exhibiting the most pronounced effects. The study demonstrates that the Casimir force can be precisely tuned to induce specific non-linear behaviors, offering new opportunities for NEMS applications. In conclusion, this research highlights the potential of Casimir force modulation to enable highly tunable, stable non-linear dynamics in NEMS, paving the way for advanced quantum sensing, actuation, and other nanoscale technologies.